Detection of diabetic polyneuropathy in a family medicine clinic by using monofilament - Lakić Biljana; Petrović Verica; Račić Maja; Stanetić Kosana (Vojnosanitetski Pregled, 2022)
Background/Aim. Diabetic polyneuropathy (DPN) is the most common microvascular complication of diabetes mellitus (DM), which may be present at the time of disease detection. Screening for DPN is performed for the patients with type 2 diabetes at the time of diagnosis and for type 1 diabetes 5 years after diagnosis. The primary aim of this study was to determine the prevalence of DNP among family medicine patients with DM aged 18 to 70 years using nylon monofilament. Methods. The cross-sectional study estimated the prevalence of DPN among primary care patients with DM in Banja Luka, Republic of Srpska, Bosnia and Herzegovina. Semmes-Weinstein nylon 10 g monofilament was used to detect DPN. Age, gender, duration of DM, type of therapy, symptoms, glycosylated hemoglobin (HbA1c), and risk factors (hypertension, smoking, dyslipidemia, obesity, physical inactivity) were analyzed. Data collection took place from June 1st, 2017 to May 31st, 2018. Results. The study included 228 patients, 132 (57.9%) men and 96 (42.1%) women. There was a statistically significant difference in the presence of all symptoms of DPN (tingling, burning, light burning, and stinging) among patients with different duration of DM (p < 0.01). Multivariate logistic regression revealed that patients who had hypertension [odds ratio (OR) = 26.2; 95% confidence interval (CI): 4.070–168.488; p = 0.001], used oral anti-diabetic therapy (OR = 12.3; 95% CI: 1.300–116.309; p = 0.029), had tingling (OR = 5.2; 95% CI: 1.431–18.571; p = 0.012) and a longer duration of diabetes (OR = 4.27; 95% CI: 1.983–9.175; p = 0.000) were more likely to have DPN. Conclusion. The prevalence of DPN in family medicine patients with DM using nylon monofilament was 24.2%. Determinants of DNP were the presence of symptoms of tingling, duration of diabetes, hypertension, and the use of oral antidiabetic therapy alone.